How Do We Recognise Problems?. Issue 1 (February 2017) - Wasser, Audrey
Abstract : This article approaches Gilles Deleuze's notion of problems through a series of thinkers Deleuze draws on in developing this notion: Heidegger, Plato, Kant, Bergson and Nietzsche. Taking these thinkers as its guide, it sketches six broad characteristics that accompany an investment in problems, ultimately arguing that problems are attained through the activity of critique. It echoes Deleuze's essay 'How Do We Recognise Structuralism?' by asking: for whom do problems exist? What does Deleuze recognise in those who recognise problems? And what do those who recognise problems make visible for us?